A Conceptual Model of Factors Affecting E-Procurement Usage and Impact among Jordanian Listed Firms: The Moderating Role of Environmental Uncertainty - Daoud, Luay; Ibrahim, Marhaiza (Journal of Advanced Research in Business and Management Studies, 2020)
E-procurement usage enables the organization to reduce business cost, access wider market and streamlining purchasing processes. Despite these benefits, the government reported showed only 32.6% of the firms in Jordan use e-procurement system. E-procurement usage among Jordanian firms still in early stage. Therefore, it is imperative to conduct further study to recognize the potential and issues of the impact of e-procurement usage on the firm performance. The population of this study consisted of firms listed on Amman Stock Exchange (ASE). Based on Diffusion of Innovations (DOI) theory, Technology, Organization and Environment (TOE) framework and the Resource-Based View (RBV) theory, authors proposed an integrated model to examine the antecedents and impact of e-procurement usage among Jordanian firms. This paper investigates the role of environmental uncertainty in the impact of e-procurement usage on firm performance. Unfortunately, the role of environmental uncertainty is nearly ignored on the impact of e-procurement usage on firm performance. Hence, this paper argues on the interaction between eprocurement usage and performance impact under the role of Environmental Uncertainty. This proposition could improve understanding e-procurement usage.